O Uso das TIC nas Práticas dos Professores de Matemática da Rede Básica de Ensino: O projeto Mapeamento e seus desdobramentos - Javaroni, Sueli Liberatti [UNESP]; Zampieri, Maria Teresa [UNESP] (FapUNIFESP (SciELO), 2015)
This article aims to present the project Mapping the use of information technology in Mathematics classes of the State of São Paulo, as well as the results of the mosaic of research that constitute this project. In addition, we present and discuss an action of continuing education that occurred in the period from August to November 2014 in the city of Bauru which refers to a university extension course. To this end, we dialogue with literature within the Mathematics Education, which points out that the use of ICT can enhance teaching and learning processes, but there are obstacles that hinder this use in schools. Then, we bring the initial results of the project, fruit of research that make it up, which follows a qualitative methodological approach. Therefore we position this course of university extension, which in turn, aimed to promote the use of ICT in the practices of mathematics teachers of Basic Education. Finally, we argue that the development of such projects enables collaborative research, which has the effect of encouraging the articulation between graduate and undergraduate students and Basic Education public schools.
The use of ICT in practice of mathematics teachers of basic education: The project Mapping and its consequences
Keywords: Collaboration; Course of University Extension; GeoGebra; Observatório da Educação (OBEDUC); Teacher Training